The Level of HbA1c Evaluates the Extent of Coronary Atherosclerosis Lesions and the Prognosis in Diabetes with Acute Coronary Syndrome. (22nd July 2022) - Xu, Shaodong; Zhou, Birong; Zhou, Bingfeng; Zheng, Jianfa; Xu, Qinghe; Wang, Bing; Fu, Minmin; Meng, Ying
Abstract : Background . The level of HbA1c can reflect the average level of blood glucose over 3 months, which is the gold standard indicator for monitoring blood glucose. The relationship between the level of HbA1c and the extent of coronary atherosclerosis lesions or the prognosis in diabetes with acute coronary syndrome (ACS) remains poorly understood. Aims . To explore whether the level of HbA1c can evaluate the extent of coronary atherosclerosis lesions or the prognosis in diabetes with acute coronary syndrome (ACS) using the SYNTAX score, the Global Registry of Acute Coronary Events (GRACE) score, left ventricular function (LVEF), left ventricular end-diastolic volume (LVEDV), and major adverse cardiac events (MACEs) in the hospital and 12 months after discharge. Methods . This study was a prospective, randomized, open-label, and parallel group study. Patients with diabetes with ACS were recruited into this study indiscriminately, and all the participants were divided into two groups according to the level of HbA1c: HbA 1 c level ≤ 7 % group and HbA 1 c level > 7 % group . The followings were used as the evaluation indicators: SYNTAX score, GRACE score, LVEF, LVEDV, and MACEs in hospital and 12 months after discharge. Results . A total of 233 patients with diabetes and ACS were enrolled and assigned to two groups according to their level of HbA1c: the HbA 1 c ≤ 7 % group (n = 92 ) and the HbA 1 c > 7 % group (n = 141 ). The results showed that the proportion of STEMI was higher in the HbA1c ≤7% group (p < 0.05 ), while the proportion of NSTEMI has not significantly higher in the HbA1c >7% group (p > 0.05 ). Regression analysis indicated that HbA1c level was significantly positively correlated with GRACE score (r = 0.156, F = 5.784, p = 0.017, n = 233 ) and SYNTAX score (r = 0.237, F = 13.788, p < 0.001, n = 233 ), and there were no statistically significant differences in LVEDV and LVEF between the two groups (p > 0.05 ). The total MACEs rate showed no significant difference between the two groups during hospitalization (p > 0.05 ) but showed significant differences at 12 months after discharge (p < 0.05 ). Conclusions . This study shows that HbA1c level was positively correlated with the extent of coronary atherosclerosis lesions and the prognosis in diabetes with ACS. The higher the HbA1c level is, the more severe the coronary atherosclerotic lesion and the worse the prognosis in diabetes with ACS are.